Bio Preservative Potential of Ocimum Basilicum L. Leaf Extract on Triplochiton Scleroxylon (K. Schum) and Ceiba Pentandra (L.) Gaertn. Wood Against Termite Attack - Okanlawon Funmilayo Busola; Olaoye Kayode Oladayo (European Scientific Journal, ESJ, 2020)
It has been reported that biopreservatives are toxic free and environmental friendly. Thus, this research paper gives account of preservative potential of Ocimum basilicum leaf extract against termite attack on Triplochiton scleroxylon and Ceiba pentandra wood. The wood sample were dimensioned by 5×5×30cm while the leaf extract was extracted using ethanol and diluted with kerosene at varying concentration ratio viz; 0:100, 25:75, 50:50, 75:25, and 100:0 %. The dimensioned wood samples were soaked for 72 hours with the prepared leaf extract hence preservative absorption rate and percentage weight loss of wood after exposure to termite were determined. Data obtained were subjected to analysis of variance at α0.05. The highest and lowest rate of absorption of the preservative was noticed with C. pentandra and T. scleroxylon having 94.48 kg/m and 38.49 kg/m respectively. The result obtained on percentage weight loss of wood samples shows that 100 % concentration of O. basilicum leaf extract had the best performance for both C. pentandra and T. scleroxylon with the lowest weight loss of 7.95 and 4.32 % respectively. Untreated wood samples of T. scleroxylon and C. pentandra recorded the highest weight loss 31.23 and 19.53 %. The result obtained show that O. basilicum leaf extract is most effective in reducing the biodegradation of T. scleroxylon and C. pentandra wood at 100 % concentration level.